Managing Hazardous Municipal Wastewater: A Membrane-Integrated Hybrid Approach for Fast and Effective Treatment in Low Temperature Environment - Pal, Parimal; Abrar, Iyman; Kumar, Ramesh (Journal of Membrane and Separation Technology, 2015)
Protection of natural water resources like lakes from the onslaught of hazardous municipal wastewater is often a challenge particularly in the cold regions. For treatment of enormous quantity of municipal wastewater, biological treatment is normally adopted but high COD (Chemical Oxygen demand) of such wastewater turns biological treatment slow and difficult. At low temperature environment, effective treatment of such municipal wastewater becomes extremely difficult due to weakened microbial activities. The present study was carried out with a hybrid approach comprising chemical treatment and membrane separation under psychrophilic conditions. Well–known Fenton’s treatment was adopted under response surface optimized conditions that helped recovery of nitrogen and phosphorus nutrients as value–added struvite fertilizer or magnesium ammonium phosphate (NH4MgPO4∙6H2O). The optimal COD removal was found to be 96% at a low temperature of 15oC and pH of 6.3 using Fe2+/H2O2 ratio of 0.10 and of H2O2 1.9 g/l with reaction time of 2 h. Down–stream purification of the struvite-free water by microfiltration and nanofiltration largely fouling–free flat sheet cross flow membrane modules ultimately turned the treated water reusable through reduction of dissolved solids, conductivity and salinity.